Management of epithelial precancerous conditions and lesions in the stomach (MAPS II): European Society of Gastrointestinal Endoscopy (ESGE), European Helicobacter and Microbiota Study Group (EHMSG), European Society of Pathology (ESP), and Sociedade Portuguesa de Endoscopia Digestiva (SPED) guideline update 2019 - Pimentel-Nunes, Pedro; Libânio, Diogo; Marcos-Pinto, Ricardo; Areia, Miguel; Leja, Marcis; Esposito, Gianluca; Garrido, Monica; Kikuste, Ilze; Megraud, Francis; Matysiak-Budnik, Tamara; Annibale, Bruno; Dumonceau, Jean-Marc; et al. (Endoscopy, 2019)
Main Recommendations Patients with chronic atrophic gastritis or intestinal metaplasia (IM) are at risk for gastric adenocarcinoma. This underscores the importance of diagnosis and risk stratification for these patients. High definition endoscopy with chromoendoscopy (CE) is better than high definition white-light endoscopy alone for this purpose. Virtual CE can guide biopsies for staging atrophic and metaplastic changes and can target neoplastic lesions. Biopsies should be taken from at least two topographic sites (antrum and corpus) and labelled in two separate vials. For patients with mild to moderate atrophy restricted to the antrum there is no evidence to recommend surveillance. In patients with IM at a single location but with a family history of gastric cancer, incomplete IM, or persistent Helicobacter pylori gastritis, endoscopic surveillance with CE and guided biopsies may be considered in 3 years. Patients with advanced stages of atrophic gastritis should be followed up with a high quality endoscopy every 3 years. In patients with dysplasia, in the absence of an endoscopically defined lesion, immediate high quality endoscopic reassessment with CE is recommended. Patients with an endoscopically visible lesion harboring low or high grade dysplasia or carcinoma should undergo staging and treatment. H. pylori eradication heals nonatrophic chronic gastritis, may lead to regression of atrophic gastritis, and reduces the risk of gastric cancer in patients with these conditions, and it is recommended. H. pylori eradication is also recommended for patients with neoplasia after endoscopic therapy. In intermediate to high risk regions, identification and surveillance of patients with precancerous gastric conditions is cost-effective.